Frequency of Contributing Factors behind Parental Refusal for Lumbar Puncture in Children in a Tertiary Care Hospital - Lubna Riaz, Aamer Naseer, Shazia Sukhera, Faiqa Taj, Faryad Hussain, Umaima Bint-e-Rehan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of contributing factors behind parental refusal for lumbar puncture in children. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Paediatrics, Jinnah Hospital Lahore and Shaikh Zayed Hospital, Lahore from 1st January 2021 to 30th June 2021. Methodology: One hundred and thirty nine parents whose children met the screening requirement were enrolled. Children’s age, sex, parent’s educational status and socio-economic position, were recorded. Parents’ reasons for refusing lumbar puncture (as defined by operational standards) were recorded. Results: There were 63.3% males and 36.7% females with mean age 4.9±3.02 years. According to contributing factors, 70% of parents thought it is risky while 12% were afraid of the needle, 34% had a terrible experience and 23% didn’t want an intrusive technique. Conclusion: The chief factor for parents’ discontent with lumbar puncture in their kids was that it’s a hazardous treatment. Most parents are uninformed of the value of lumbar puncture in assessing and treating children, it appears that the higher the parent’s awareness leads to more positivity they have in this respect.